The Influence of Standards and Contextual Approach on Civics Achievement with Learning Motivation Mediation - Kamsin, Kamsin; Nuryanto, Uli Wildan; Handayani, Yolla Sukma (Jurnal Lingua Idea, 2025)
In order to build a conducive learning atmosphere and support learning effectiveness, a strategy is needed to utilize appropriate and relevant teaching materials. One of the steps that can be taken is to choose a contextual-based teaching material PAKEM learning model. The PAKEM learning model and contextual approach are considered to be able to accommodate learning that is in line with the expected learning objectives. This study used public elementary schools located in Carenang District as samples. The research data were 16 schools with a total sample of 165 samples. The data used in this study consists of primary data obtained through questionnaires, observations, and documentation, as well as quantitative data that is cross-sectional in nature with measurements using a Likert scale. The data was analyzed using the inferential method with the Warp PLS application version 8.0. The results of the study showed that the PAKEM model and contextual approach influenced learning achievement and motivation, and learning motivation mediated the influence of both on learning achievement.